Pengaruh Manajemen Sumber Daya Manusia terhadap Kuantitas Tenaga Kerja Perusahaan di Perusahaan Bidang Jasa Event Organizer (Studi Kasus PT. BOAK GLOBAL SMARTINDO) - Ramadani, Zulfan; Arnu, Anggi Pasca (Jurnal Ilmiah Wahana Pendidikan, 2025)
Human Resource Management has become important for Companies where it can influence Company Finance but by managing its People or Workforce. This research uses a case study at PT. BOAK GLOBAL SMARTINDO to find out how Human Resources Management influences the Quantity of its Workforce. This research uses quantitative research methods with a case study approach and is followed by materials including primary, namely internship reports, secondary, namely previous research journals and tertiary materials, namely from the internet and other sources.